A Project Report on Retrival of Encrypted Data from Cloud using TOp-k Method - SAMIULLA, SRIDHAR, PRASHANTH and AJEETH (2013)
INTERNAL GUIDE:TAMILARASH R, MVJCE EXTERNAL GUIDE
Keywords: Retrival of Encrypted Data from Cloud using TOp-k Method